Addressing Anti-Black Racism in the Library and Information Science Curriculum: A Canadian-Centric Learning Model - Matthews, Amber (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2025)
Canadian communities are facing a crisis of inequity, and library service providers must do more to respond to the causal conditions of anti-Black and other forms of systemic racism (Black & Mehra, 2023). Beginning in 2022, the first known Canadian MLIS course, Anti-Racism in Library and Information Science, was piloted at Western University. It aimed to allow students to engage with transformative and collaborative anti-racism frameworks relevant to the Canadian library sector and MLIS curriculum. The one-semester (13-week) course was offered once each summer in 2022 and 2023. The multi-faceted course aimed to equip students with community-based approaches to learning in partnership with local Black communities. As exemplars, the course approach and learnings also allow LIS scholars and practitioners to explore and evaluate their understanding of community-based and anti-racist frameworks. This paper provides evidence-based research and Black-centred resources that can begin to address anti-Black and other forms of systemic racism impacting Canadian library communities. The Canadian-centric and LIS-tailored approach can further benefit both library and community organizations by supporting anti-racism efforts to uncover covert practices of anti-Black racism in personal and professional practices and worldviews.